Cultura, alineamiento y perdurabilidad empresarial (2016)
A turbulent and highly uncertain environment is permanent condition of the organizations. This condition confronts them with the following challenge: how to endure and what would be the contribution of people (both those involved in the management of the company, and stakeholders) in this scenario? It could be affirmed, in response, that the contribution is wide-ranging, especially from categories such as mobilization of human resources, organizational climate and leadership, among others. However, the concept that most closely relates to the human factor in organizations is organizational culture, which is understood as “the values and behaviors that contribute a unique psychosocial environment, they provide more or less cohesion to the organization and, in turn, better focus and unity of purpose” (Business Dictionary, 2015).The organizational culture uses the concept of alignment, in order to give a coherent response to the relationship between the strategic objectives of the organization and the personal goals of those who have direct or indirect relationship with the organization. Such alignment includes both the concept of resilience, so associated with the need to last, in a competitive manner, in time. The purpose of the article is to analyze the factors which contribute to the resilience of contemporary organizations, and particularly the elements that affect their disappearance in a context characterized by the rapid increase in the degree of concentration of ownership and organizational gigantism.